Penerapan Metode Iqra’ dalam Pembelajaran Membaca Alquran - Nur Hasnah; Indah Muliati (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to examine the application of the iqra' method in learning to read the Qur'an. This study used a qualitative method with a descriptive analysis approach, research data were taken through direct interviews with 7 informants. To strengthen the interview data, the writer made observations by looking directly at the process of learning to read the Qur'an using the Iqra' method. The data obtained were then analyzed by data reduction, data presentation, and drawing conclusions, after which a technique was used to test the validity of the data using source triangulation, which was not only taken from one source but there were several sources of information that supported this research including, the head of MDA, teachers, and students of Tarbiyah Islamiyah 3 Nagari Kayutanam. The results showed that: the application of the iqra' method in learning to read the Qur'an was carried out by The teacher explained, read the single hijaiyyah letters, continued, long and short in front of the class using the blackboard, then the students followed together, then the students read one by one in front of the class using the iqra' book. inhibiting factors for learning to read the Qur'an, namely students who rarely enter class will miss the learning process and even forget the hijaiyyah letters that have been studied previously, supporting factors for the learning process, namely teachers who are always patient and istiqamah in teaching students until students really able to read the Qur'an properly and correctly. The findings in this study have proven that the application of learning to read the Qur'an using the iqra' method at MDA Tarbiyah Islamiyah 3 Nagari Kayutanam is in accordance with the existing iqra' method theory and coupled with the creativity of the teacher.